Surface Modification of Black Phosphorus with Group 13 Lewis Acids for Ambient Protection and Electronic Tuning. (5th March 2021) - Tofan, Daniel; Sakazaki, Yukako; Walz Mitra, Kendahl L.; Peng, Ruoming; Lee, Seokhyeong; Li, Mo; Velian, Alexandra
Abstract: Herein we introduce a facile, solution‐phase protocol to modify the Lewis basic surface of few‐layer black phosphorus ( b P) and demonstrate its effectiveness at providing ambient stability and tuning of electronic properties. Commercially available group 13 Lewis acids that range in electrophilicity, steric bulk, and Pearson hard/soft‐ness are evaluated. The nature of the interaction between the Lewis acids and the b P lattice is investigated using a range of microscopic (optical, atomic force, scanning electron) and spectroscopic (energy dispersive, X‐ray photoelectron) methods. Al and Ga halides are most effective at preventing ambient degradation of b P (>84 h for AlBr3 ), and the resulting field‐effect transistors show excellent IV characteristics, photocurrent, and current stability, and are significantly p‐doped. This protocol, chemically matched to b P and compatible with device fabrication, opens a path for deterministic and persistent tuning of the electronic properties in b P. Abstract : A match made for black P: Modifying black P with chemically‐matched Lewis acids imparts remarkable ambient stability, excellent transport properties, and persistent p‐doping. Compatible with device fabrication and relying on commercially available reagents, this facile protocol opens a path for deterministic and persistent tuning of electronic properties in black P.